Trends (2020–2022) toward Reduced Prevalence of Postcoronavirus Disease Syndrome and Improved Quality of Life for Hospitalized Coronavirus Disease 2019 Patients with Severe Infection and Venous Thromboembolism - Bozzani, Antonio; Arici, Vittorio; Tavazzi, Guido; Ragni, Franco; Mojoli, Francesco; Cavallini, Elena; Vugt, Floris van; Cutti, Sara; Figini, Silvia; Venturi, Alessandro; Sterpetti, Antonio V.; Arbustini, Eloisa (Seminars in Thrombosis and Hemostasis, 2023)
The coronavirus disease 2019 (COVID-19) pandemic seems to be at its end. During the first outbreak, alfa was the dominant variant, and in the two following years, delta was the dominant variant. Questions remain about the prevalence and severity of post-COVID syndrome (PCS). We compared the medium-term outcomes of a selected group of patients considered at high risk for PCS: hospitalized patients with severe COVID-19 infection who presented clinical evidence of the acute onset of venous thromboembolism. Weighted Cox regression was used to estimate the adjusted hazard ratios for the risk of early and medium-term complications and quality of life (QoL) in COVID-19 patients developing acute venous thrombo-embolism according to the period of admission to the hospital. The primary outcome was the modification of QoL at a median follow-up of 24 months in patients hospitalized for COVID-19. The secondary outcome was the modification of QoL related to COVID-19 severity. The absolute risk of mortality for hospitalized COVID-19 patients was higher during the first outbreak (risk difference, 19% [95% confidence interval [CI], 16–22%]). Patients with acute onset of thromboembolism during the first outbreak had increased mortality, hospital stay, and need for intensive care unit treatment (p < 0.01). In patients who suffered from severe COVID-19 infection and thromboembolism in the following 2 years, symptoms during follow-up were less common and milder (risk difference 45% [95% CI, 40–52%]. In total, 19 patients were alive at 24 months follow-up: 12 patients (63%) reported important physical symptoms and 10 patients (52%) relevant emotional/mental symptoms. All patients reported reduced QoL in comparison with the preinfection time; in 15 patients (79%), the reduced QoL limited significantly their social and work activities. All patients reported permanent worsening of QoL after discharge from the hospital. Comparing the three different February to April interval years (2020, 2021, and 2022), patients reported a somewhat worse perception of health condition in comparison with the preinfection time, respectively, in 100, 79, and 56% respectively. The findings of our study show reduced prevalence and severity of PCS in the last 2 years. Less virulent variants, herd immunity, and vaccination may played a significant role.
Keywords: COVID-19; quality of life; thrombosis; survival; median follow-up